Mental health literacy: A systematic review of knowledge and beliefs about mental disorders in Malaysia - Khadeeja, Munawar; Firdaus Mukhtar; Fahad, Riaz Choudhry; Ng, Alvin Lai Oon * (Wiley, 2022)
Background: Mental health problems in Malaysia are on a rise. This study aimed at performing a systematic review of mental health literacy (MHL) in Malaysia.